2006
DOI: 10.1111/j.1440-0960.2006.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of adult patients with cutaneous leukocytoclastic vasculitis

Abstract: A retrospective analysis was conducted on 93 adult patients with cutaneous leukocytoclastic vasculitis from St. Vincent's Hospital Melbourne to determine the classification, aetiology, severity and prognosis of this population of patients. We developed a new classification system for the purposes of our study based on modifications to the Chapel Hill Consensus Conference definitions for vasculitic syndromes. The results of our study indicate that an obvious cause was not found in 44.1% of patients. Of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
4
22

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 24 publications
7
44
4
22
Order By: Relevance
“…Equally important is the absence of any underlying cause or association that could be identified for this group of patients, consistent with recent reports in which about 40-60% of all cases of cutaneous vasculitis are idiopathic [5][6][7][8][9][10][11][12] . The low incidence of HSP in this study is reflective of the fact that HSP mainly involves children [5] in accordance with other studies [1,5,7] . Drugs and infections contributed to cutaneous vasculitis in 31.6% of our patients, which is consistent with a previous report by Carlson et al [5] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Equally important is the absence of any underlying cause or association that could be identified for this group of patients, consistent with recent reports in which about 40-60% of all cases of cutaneous vasculitis are idiopathic [5][6][7][8][9][10][11][12] . The low incidence of HSP in this study is reflective of the fact that HSP mainly involves children [5] in accordance with other studies [1,5,7] . Drugs and infections contributed to cutaneous vasculitis in 31.6% of our patients, which is consistent with a previous report by Carlson et al [5] .…”
Section: Discussionsupporting
confidence: 90%
“…Tai et al [7] reported an incidence of 61.3%, which is higher compared to the present study. This might be explained by the fact that different researchers may use varying definitions of the vasculitic syndromes for classifying patients in different categories, such as the American College of Rheumatology criteria and the Chapel Hill Congress Conference definitions, which identify different patients [5,6,[8][9][10][11] .…”
Section: Discussioncontrasting
confidence: 78%
“…It has been estimated that in 45% to 55% of cases of LCV a cause remains unknown. 10,15 Other common causes of LCV include infection, ACTD, drug reactions, and malignancy. Our study had more cases that were idiopathic compared with the literature, and no cases were associated with malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytoclastic vasculitis can be associated with malignancy or collagen vascular disease, but about half of cases are idiopathic. 2 Henoch-Schönlein purpura is a well-known form of leukocytoclastic vasculitis, but is more common in children, and generally evoked by viral illness. HenochSchönlein purpura may be associated with joint or kidney involvement and malignancy in older men, so an accurate diagnosis is critical.…”
Section: Discussionmentioning
confidence: 99%